Monosynaptic Input Mapping of Diencephalic Projections to the Cerebrospinal Fluid-Contacting Nucleus in the Rat - Song, Si-Yuan; Li, Ying; Zhai, Xiao-Meng; Li, Yue-Hao; Bao, Cheng-Yi; Shan, Cheng-Jing; Hong, Jia; Cao, Jun-Li; Zhang, Li-Cai (Frontiers in Neuroanatomy, 2020)
Objective: To investigate the projections the cerebrospinal fluid-contacting (CSF-contacting) nucleus receives from the diencephalon and to speculate on the functional significance of these connections. Methods: The retrograde tracer cholera toxin B subunit (CB) was injected into the CSF-contacting nucleus in SD rats according to the experimental formula of the stereotaxic coordinates. Animals were perfused 7–10 days after the injection, and the diencephalon was sliced at 40 μm with a freezing microtome. CB-immunofluorescence was performed on all diencephalic sections. The features of CB-positive neuron distribution in the diencephalon were observed with a fluorescence microscope. Results: The retrograde labeled CB-positive neurons were found in the epithalamus, subthalamus, and hypothalamus. Three functional diencephalic areas including 43 sub-regions revealed projections to the CSF-contacting nucleus. The CB-positive neurons were distributed in different density ranges: sparse, moderate, and dense. Conclusion: Based on the connectivity patterns of the CSF-contacting nucleus that receives anatomical inputs from the diencephalon, we preliminarily assume that the CSF-contacting nucleus participates in homeostasis regulation, visceral activity, stress, emotion, pain and addiction, and sleeping and arousal. The present study firstly illustrates the broad projections of the CSF-contacting nucleus from the diencephalon, which implies the complicated functions of the nucleus especially for the unique roles of coordination in neural and body fluids regulations.